2007
DOI: 10.1016/j.ijid.2007.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarticular complications of brucellosis in Hamedan, an endemic area in the west of Iran

Abstract: Osteoarticular disease is the most common complication of brucellosis in Western Iran. Sacroiliitis is the most common form of osteoarticular complication. With the use of a proper treatment regimen, the prospect for recovery is good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
2
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 20 publications
5
39
2
7
Order By: Relevance
“…In the present study, the manifestations of localized brucellosis, including peripheral arthritis and sacroilietis, were mentioned in 10 (12%) and 20 (24.1%) patients, respectively. Although peripheral arthritis was mentioned as the most prevalent osteoarticular complain of brucellosis in some studies (14,15), in other studies like the present research, sacroileitis was found as the most common musculoskeletal complication (16).…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…In the present study, the manifestations of localized brucellosis, including peripheral arthritis and sacroilietis, were mentioned in 10 (12%) and 20 (24.1%) patients, respectively. Although peripheral arthritis was mentioned as the most prevalent osteoarticular complain of brucellosis in some studies (14,15), in other studies like the present research, sacroileitis was found as the most common musculoskeletal complication (16).…”
Section: Discussionmentioning
confidence: 41%
“…Anemia, leukopenia, thrombocytopenia, leukocytosis, thrombocytosis, and elevated ESR were detected in patients with brucellosis in previous studies (12,16,21,24). Anemia, which was found in 44 (53%) patients, was found as the most common hematological abnormality in the present study.…”
Section: Discussionmentioning
confidence: 71%
“…According to various studies, the frequency of osteoarticular complications has been reported in 10 to 80 % of patients (14,15). In a previous study in our region, the frequency of osteoarticular complications was 28.5%, of which 75.7% cases were of sacroiliitis (16). Laboratory diagnosis is based on culture, serology, and PCR.…”
Section: Discussionmentioning
confidence: 89%
“…Brucellosis is a public health problem in many developing countries [39]. In many brucellosis-endemic countries, health systems are not well-organized and the cases are considerably under-reported.…”
Section: Epidemiology and Distributionmentioning
confidence: 99%